Pt surface segregation in L10-FePt nano-grains. (1st July 2017) - Sepehri-Amin, H.; Iwama, H.; Hrkac, G.; Butler, K.T.; Shima, T.; Hono, K.
Abstract: The influence of the chemical compositions of FePt films on the surface segregations of Pt was investigated by cross-sectional high angle annular dark field (HAADF) scanning transmission electron microscopy (STEM) of L10 -FePt granular films grown on single crystalline MgO substrates. Ab initio atomistic simulations revealed the surface segregation of Pt is detremental for the magentocrystalline anisotropy energy of the L10 -FePt grains. This detremental effect is pronounced for the grain size of less than 15 nm. We found that the Pt surface segregation can be suppressed by a trace addition of Ag to the FePt film. Graphical abstract: